(untitled) (International Journal of Medical and Surgical Sciences, 2015)
Commonly after the early loss of teeth, extractions, presence of periodontal disease, or pneumatization of the sinus cavities, bone resorption occurs leading to atrophy of the alveolar ridge. This presents several challenges from the point of view of implant and rehabilitation when planning implant placement and rehabilitation. However at present the procedures for the solution of these problems with the use of bone graft, either autologous or xenograft allow predictable results. The aim of this case report is to describe the surgical procedures prior to the comprehensive rehabilitation treatment of female patient, 53 years old, partially toothed jaw and mandibular teeth overall. The extraction of all the upper teeth along the jaw ridge preservation using autogenous graft and xenograft bone tissue, besides the left maxillary sinus lift, culminating with the insertion of an immediate acrylic maxillary prosthesis was performed.